Information Security Evaluation Using Case Study Information Security Index on Licensing Portal Applications - Wardhani, Widiastuti Kusumo; Soewito, Benfano; Zarlis, Muhammad (Universitas Bina Darma, 2023)
There's a lot of cyber attacks going on right now, so the Ministry of Public Works and People's Housing (PUPR) has to get serious about preventing them. One of the information system that contains critical public data need to be secured is Portal Perizinan. In order to maintain information security, an evaluation should be carried out to assess the level of readiness (comprehensiveness and consistency) of the implementation of information security based on the SNI ISO/IEC 27001:2013 criteria using the Information Security Index. (KAMI Index). The five areas assessed aim to determine the level of organization preparedness in the implementation of information security. Obtained a score of 31 for the level of organization dependence on electronic systems, with a high level of category. The presence of technology security is at level I through to level II and our index measures 351, which means that the level of maturity of the new ISMS is at the stage of Achievement of the Basic Framework. From the results of this case study it can be seen that the state of information security readiness in the Ministry of PUPR still needs to be improved to meet ISO 27001 standard.